1865 Del. Laws 930, An Act to Prevent the Loading of Gunpowder Within Certain Distances of Railroads, chap. 554, § 1 - (:unkn) unknown (General Publisher, 1865)
Prohibited loading gun powder into any rail cars within one hundred yards of the track used for carrying passengers.Violators fined one thousand dollars and imprisoned six months.
--
Keywords: GUN POWDER TRANSPORTATION